A Survey of Query Expansion, Query Suggestion and Query Refinement Techniques - Ooi, Jessie; Hongwu, Qin; Ma, Xiuqin; Siau-Chuin, Liew (2015)
The ineffectiveness of information retrieval systems often caused by the inaccurate use of keywords in a query. In order to solve the ineffectiveness problem in information retrieval systems, many solutions have been proposed over the years. The most common techniques are revolving around query modification techniques such as query expansion, query refinement, etc. Due to the high similarity in these query modification techniques, people are often confused about their differences. However, few existing survey papers compare their differences. Hence, in this paper, we first briefly discuss the basic technique of query expansion, query suggestion and query refinement, and then make a detailed comparison between these three techniques. We finally show the promising future research trend in the field of query modification.